The impact of financial crises on changes to the models of corporate governance - Stanisław Rudolf (International Journal of Management and Economics, 2021)
This study aims to define the impact of two largest crises of 1997-1998 and 2007-2008 on changes to the models of corporate governance. In order to achieve the assumed aim, a critical analysis of specialist literature and relevant legal regulations has been applied. The analysis is focused on changes in the main models of corporate governance, namely: in the Anglo-Saxon (monistic) model and in the German (dualistic) model. Generally, they can be defined as of evolutionary nature but some deeper changes have taken place under the influence exerted by the above-mentioned crises. The latter crisis has emphasized the important role of corporate governance in banks and other financial institutions. Changes in corporate governance are largely affected by international institutions or organizations, such as the Organization for Economic Cooperation and Development (OECD) or the European Commission. Their recommendations and guidelines have contributed to the dissemination of so-called good practice codes. The considerations presented below allow the author to state that in both analyzed models of corporate governance, changes occur in the same or similar direction lines (the phenomenon of convergence). It can be also observed that the first analyzed crisis has caused larger changes in the monistic model, whereas the second crisis has affected the dualistic model in a more significant way.
Keywords: G21; G34; H12; 650; convergence; corporate governance; financial crisis; good practice codes; the OECD principles